Strategy to Increase the Effectiveness of Subsidized Fertilizer Distribution: A Case Study in Indramayu Regency, West Java. Issue 1 (1st April 2022) - Hatta, Muhammad; Mujahidin Fahmid, Imam; Salman, Darmawan; Kurniaty,
Abstract: The effectiveness of the distribution of subsidized fertilizers in Indramayu Regency is still experiencing problems at the beginning of the rice planting season. This study aims to analyze: timely and targeted aspects in distributing subsidized fertilizers, implementation of the Farmer's Card, and strategies to increase the effectiveness of subsidized fertilizer distribution. The study was conducted in Indramayu Regency, 2020. Primary data were collected from respondents: 25 lowland rice farmers, 1 fertilizer stall and 1 fertilizer distributor. In addition, secondary data was also collected. Data analysis was carried out quantitatively and qualitatively. The results showed: (1) Approximately 85% of farmer respondents stated that subsidized fertilizers were available at the stall when needed, and the rest stated that there were still delays; (2) Farmer's Cards are one of the efforts to increase the effectiveness of subsidized fertilizer distribution, (3) Farmer's Cards in Indramayu have been printed as many as 12, 771 farmer groups, and about 89.25% have been distributed. Strategies to increase the effectiveness of subsidized fertilizer distribution are: facilitation of subsidized fertilizer stall capital, especially those owned by farmer groups, increasing the implementation of Farmer's Cards for subsidized fertilizer distribution and gradual improvement of the Electronic Data for the Definitive Plan for Group Needs.